Following The Prophet Muhammad Character through Ngabuleh Tradition in Pondok Pesantren Darul Ulum Banyuanyar Pamekasan - Moh. Wardi; Ismail Ismail (UIN Maulana Malik Ibrahim Malang, 2018)
This research is part of the relevance of personality character of the Prophet Muhammad with the ngabuleh tradition in the theory of FAST (fathanah, amanah, siddiq, and tabligh). The purpose of this study is to find out and explain the ngabuleh tradition in religious, cultural, and economic reviews. The study is categorized in phenomenological research using qualitative approach. The data were obtained from observation, in-depth interview, and documentary study. It was then analyzed by data reduction, data presentation, and conclusion phase. Informant in this study is kabuleh in Pondok Pesantren Darul Ulum at Banyuanyar District, Pamekasan Regency. The results show that,in the view of religion ngabuleh is the implementation of Islamic values about following the character of the Prophet Muhammad and sincerity. Culturally, as a form of adherence of high respect to the pillars of culture in Madura, namely bhuppa’-bhabhu’-ghuru-rato (father, mother, teacher/kiai and queen/government). Economical-wise, ngabuleh is a kind of paying respect to the kiai by working in the corporate run by kiai/Pesantren and at once, contributing santri’s skill and competence in the field of entrepreneur.Penelitian ini merupakan bagian dari relevansi karakter kepribadian Nabi Muhammad dengan tradisi kabuleh dalam teori FAST (fathanah, amanah, siddiq, and tabligh). Tujuan penelitian ini adalah untuk mengetahui dan menjelaskan tradisi ngabuleh dalam tinjauan agama, budaya, dan ekonomi. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan jenis penelitian fenomenologis. Data diperoleh dari hasil observasi berperan serta, wawancara mendalam, dan studi dokumentasi. Analisis data dilakukan dengan reduksi data, penyajian data, dan tahap kesimpulan. Informan dalam penelitian ini kabuleh di Pesantren Darul Ulum Banyuanyar Pamekasan. Hasil penelitian menunjukan bahwa, secara agama, ngabuleh merupakan implementasi nila-nilai ajaran Islam tentang keteladanan sifat Nabi, dan keikhlasan. Secara budaya, sebagai bentuk kepatuhan penghormatan yang tinggi kepada pilar-pilar penyangga kebudayaan Madura, yakni bhuppa’-bhabhu’-ghuru-rato (bapak, ibu, guru/kiai, ratu/pemerintah). Secara ekonomi, bahwa kabuleh yang berkhidmat kepada kiai dengan bekerja pada usaha milik kiai/pesantren memberikan kontribusi skill dan kompetensi santri dalam bidang entrepreneur.